Basketball VO2max Level Identification - Ghana Firsta Yosika; Maharani Fatima Gandasari; Y. touvan juni samodra; Putra Sastaman B; Davi Sofyan; Noer Riswandi (Universitas Majalengka, 2023)
This study aims to determine the level of Maximum Oxygen Volume (VO2Max) in Men's Basketball Athletes in Porcupine District for Preparation for West Kalimantan Provincial Sports Week (PORPROV) 2022. The method used in this research is to use a quantitative descriptive method. The form of research used is a test using the Bleep Test. The analysis used calculates calculating the percentage of the results obtained. Respondents in this study were PORPROV At athletes in the Men's Basketball Branch of the Porcupine District. From the results of the study, it was found that the maximum oxygen volume level in Men's Basketball Sports Athletes in Porcupine District showed 11 players (55%) in the Less category and nine players (45%) in enough category. From the results of the VO2max test in Men's Basketball Athletes in Landak District, it showed that most players had a maximum oxygen volume level in the less category.